PERAN GAYA HIDUP TERHADAP KEPUTUSAN PEMBELIAN DI CAFE ORANGAE PUNCAK PADANJESE - Farela, Gio Fany (JURNAL ILMU MANAJEMEN UNIVERSITAS TADULAKO, 2020)
This research aims at finding out the influence of the lifestyle simultaneously and partially on the purchasing decision?s at the Cafe Orange Puncak Padanjese. The research subjects were 60 respondent, with the sampling technique used is purposive sampling. The data were taken through questionnaire, observation, and interview. Multiple Regression Analysis model was used to analyze the data. The results show that: 1) Lifestyle that consisted of dimensions of activity, interest and opinion simultaneously gives significant influence on the decision in purchasing at Cafe Orange Puncak Padanjese. 2) Dimension of activity partially give significant influence on the decision in purchasing at Cafe Orange Puncak Padanjese. 3) Dimension of interest partially give significant influence on the decision in purchasing at Cafe Orange Puncak Padanjese. 4) Dimension of opinion partially give significant influence on the decision in purchasing at Cafe Orange Puncak Padanjese.Keywords: Lifestyle, Activities, Interest, Opinion, Decision Purchasing